An Analysis Of English Teacher’s Classroom Assessment At School (A Case Study At Smpn 1 Blangpidie) - Misra Misra; Meristika Moetia (Universitas Dehasen Bengkulu, 2023)
This study aims to explore and describe the assessment process and how English teachers apply the three aspects of assessment according to the Ministry of Education and Culture. It was a descriptive qualitative method. The sample consisted of five English teachers at SMPN 1 Blangpidie. The techniques of data collection were observation, interviews, and documentation. The technique of analyzing data researcher used three steps, there are: 1) data reduction; 2) data presentation, and 3) drawing conclusions and verification. The results showed that the assessment process carried out by the English teachers at SMPN 1 Blangpidie run well. The assessment of three aspects of cognitive, affective, and psychomotor has also been successfully carried out during face learning. Meanwhile, based on the result of interview with the teachers, the most of them used formative assessment as reward given to the students’ and this assessment can increase student motivation skill. However, there are several obstacles in the class assessment process such as there are still students who did cheating while assessment run but it could be calculated the amount of students did not only a few and to face this case the teachers give them motivation do not do it again in the next assessment.